MOE/RF: A Novel Phishing Detection Model Based on Revised Multiobjective Evolution Optimization Algorithm and Random Forest - Zhu, Erzhou; Chen, Zhile; Cui, Jie; Zhong, Hong (IEEE eTransactions on network and service management, 2022)
To effectively boost computer usage, machine learning models are used in several phishing detection systems to classify enormous phishing datasets. Based on phishing patterns, researchers prefer to extract a considerable number of features to improve phishing detection performance. However, redundant and useless features in the feature set degrade the performance of the underlying classification models. In addition, several existing phishing detection models mainly focus on detection accuracy and overlook recall rates. However, in phishing detection, it is more harmful to falsely detect a phishing website as a legitimate website than it is to detect a legitimate website as a phishing website. This study proposes a novel phishing detection model, multi-objective evolution/random forest (MOE/RF), which is based on the revised multi-objective evolution optimization algorithm (MOE) and random forest (RF). The MOE/RF model uses accuracy as the detection target and minimizes the probability of false detection of phishing sites. In addition, two new strategies, the symmetric uncertainty-based population initialization and the population state-based adaptive environmental selection, are proposed to improve the performance of the MOE. Experimental results on testing five different phishing datasets demonstrated that the MOE/RF performs superior to several existing methods.